2008
DOI: 10.1152/ajpendo.90450.2008
|View full text |Cite
|
Sign up to set email alerts
|

Changes in insulin sensitivity during leptin replacement therapy in leptin-deficient patients

Abstract: Leptin replacement rescues the phenotype of morbid obesity and hypogonadism in leptin-deficient adults. However, leptin's effects on insulin resistance are not well understood. Our objective was to evaluate the effects of leptin on insulin resistance. Three leptin-deficient adults (male, 32 yr old, BMI 23.5 kg/m 2 ; female, 42 yr old, BMI 25.1 kg/m 2 ; female, 46 yr old, BMI 31.7 kg/m 2 ) with a missense mutation of the leptin gene were evaluated during treatment with recombinant methionyl human leptin (r-metH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 70 publications
(78 reference statements)
1
37
0
Order By: Relevance
“…(6), Elif A. Oral and Charles Burant discuss the findings of our paper recently published in AJP-Endocrinology and Metabolism, titled "Changes in insulin sensitivity during leptin replacement therapy in leptin-deficient patients" (7). In that letter, they cite the DISCUSSION in our article and present data that support the hypothesis that the increase in insulin sensitivity, while off recombinant methionyl human leptin, can be attributed to the rapid expansion of the adipose tissue mass.…”
mentioning
confidence: 66%
“…(6), Elif A. Oral and Charles Burant discuss the findings of our paper recently published in AJP-Endocrinology and Metabolism, titled "Changes in insulin sensitivity during leptin replacement therapy in leptin-deficient patients" (7). In that letter, they cite the DISCUSSION in our article and present data that support the hypothesis that the increase in insulin sensitivity, while off recombinant methionyl human leptin, can be attributed to the rapid expansion of the adipose tissue mass.…”
mentioning
confidence: 66%
“…Leptin affects insulin sensitivity and might have fascillatory action on insulin secretion as in our subject during the early phase of leptin treatment sharp increases of insulin occurred in response to meals while at a later time point, insulin levels decreased. Although these seem like contradictory findings of leptin effects on insulin secretion and resistance, one needs to be aware that most of the interactions of leptin within the adipoinsular axis have been studied in vitro and in animal models [24]. Some animal studies showed that leptin increases insulin resistance [25, 26], other documented a decrease in insulin resistance [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our results are consistent with effects observed in clinical studies during which continued leptin replacement in leptin-deficient individuals was associated with reduced insulin levels. Similarly, the insulin-sensitizing effects of leptin replacement have been demonstrated in patients with lipodystrophy [24, 29, 30]. This suggests that relative hyperleptinemia during the early phase of leptin treatment may potentially contribute to increased insulin resistance [24] and plasma leptin may have an independent effect on insulin sensitivity which is not directly explained by adiposity or hyperinsulinemia [31].…”
Section: Discussionmentioning
confidence: 99%
“…This is corroborated by recent clinical and animal investigations that excess as well as complete absence of fat in the body are concomitant with hyperinsulinemia, insulin insensitivity and diabetes. 7,[22][23][24][25][26][27][28] The discovery of insulin in 1922 and the subsequent development of insulin analogs have been the life-saving treatments of hyperglycemia and in delaying or preventing the array of chronic complications of diabetes mellitus. 2,13,[29][30][31] Diabetes, therefore, has traditionally been viewed as an affliction of either lack of or incomplete use of insulin and, consequently, conventional research has focused entirely on improving ways to deliver insulin for precision in attaining glycemic control to simulate the physiological range of blood glucose, necessary to combat the comorbidity cluster of this chronic malady.…”
Section: Introductionmentioning
confidence: 99%
“…22,27,52 Similarly, lipoatrophy and leptin deficiency due to wasting inflicted by human immunodeficiency virus infection and treatment of human immunodeficiency virus-infected patients with antiretroviral treatment, are associated with insulin insensitivity and diabetes, both improved by daily leptin replacement. 25,52,[57][58][59] Importantly, these antidiabetic effects of daily leptin replacement manifesting independent of any discernible impact on appetite and weight, involved hypothalamic leptin responsive pathways because mice with conditional leptin receptor knockout in the hypothalamus were diabetic 60 and instillation of leptin receptors selectively in the hypothalamus repressed hyperinsulinemia in the diabetic, leptin receptor mutant rats. 61 Thus, both leptin deficit and leptinopenia-induced insufficient hypothalamic leptin signaling are associated with dysregulation of the glucose-insulin axis.…”
Section: Introductionmentioning
confidence: 99%